(untitled) (Comprehensive Journal of Science, 2025)
Libyan universities are facing increasing challenges in improving the quality of education as well as academic and administrative performance. In light of these challenges, Total Quality Management (TQM) has emerged as a significant strategic approach to enhancing institutional performance. This study aims to analyze the impact of implementing TQM principles on performance improvement at Al-Jufrah University, based on the evaluations and perspectives of faculty members, who are considered among the most important stakeholders in the educational process, and to examine whether the level of university performance varies according to certain variables. The researchers employed a descriptive-analytical method to achieve the study objectives. A questionnaire consisting of 27 items was distributed to 168 faculty members, of whom 150 responded. Data were statistically processed using the Statistical Package for the Social Sciences (SPSS), applying appropriate statistical methods, including Cronbach’s Alpha, to assess reliability and validity. Statistical analysis of the data revealed a strong, positive, and statistically significant correlation between the application of TQM principles and performance improvement. The results also demonstrated a direct and substantial effect of TQM implementation on performance enhancement. Among the dimensions, customer focus ranked as the most influential, followed by top management support, and then continuous improvement. The study concluded with several recommendations, most notably the need to provide professional development programs for staff members and to ensure adequate and appropriate resources are available to achieve the objectives of the educational process. Additionally, the study recommended conducting further research in the future to explore models of TQM application in education and their relationship with various variables